PENGARUH EKSTRAK DAUN SIRIH MERAH (PIPER CROCATUM) KONSENTRASI 10%, 20% dan 40% TERHADAP PERTUMBUHAN CANDIDA ALBICANS PADA PLAT GIGI TIRUAN RESIN AKRILIK - , REIZA PRABANDANA, drg. Endang Wahyuningtyas, M.S., Sp.Pros(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Candida albicans adhesion on acrylic resin denture plate surfaces is one of the causes of denture stomatitis. Red betel leaves ( Piper crocatum ) are usually used by Indonesian people and are known to have antifungal effects. The purpose of this study is to determine the effect of red betel leaves extract with 10 % , 20 % and 40 % concentrations to the growth of Candida albicans on acrylic resin denture plate. The study was conducted using 40 samples. The samples used heat cured acrylic resin plates with a diameter of 10 mm and a thickness of 2 mm. The samples were divided into four groups. Each group was soaked with red betel leaves (Piper crocatum) extract with concentrations of 10%, 20% and 40% for 8 hours. The test was to prevent the growth of Candida albicans on acrylic resin denture plate in Saboraud's Dextrose Agar (SDA). Sterile aquadest was used as a control. The Candida albicans used in this study were pure cultures diluted with physiological saline solution to obtain the value of 108 CFU / ml. Effects of treated group on the growth of Candida albicans were determined by counting the number of colonies of Candida albicans after 24 hours of incubation using a colony counter. The results of counting the colonies of Candida albicans was analyzed with One way Annava. The result shows that the red betel leaves (Piper crocatum) extract of concentrations 10%, 20% and 40% concentrations significantly affecting the growth of Candida albicans on acrylic resin denture plate (p<0.05). The Post Hoc test result indicate a significant differences of LSD among average number of colonies on red betel leaves (Piper crocatum) extract of 10%, 20%, 40% concentrations and sterile aquadest (p<0.05). It can be concluded that the red betel leaves (Piper crocatum) extract of 10%, 20%, and 40% concentrations can inhibit the growth of Candida albicans on acrylic resin denture plate. Extract of red betel leaves (Piper crocatum) with 40% concentration has the highest effect of inhibiting the growth of Candida albicans on acrylic resin denture plate.